Implementation of appropriate technology programs in Tanjung Batu Village, Kutai Kartanegara, to realize an environmentally friendly independent village - Surahman, Surahman; Ali, Sudirman; Adhiksana, Arief; Regiyana, Yuan; Hayati, Nuria (Community Empowerment, 2021)
This community service program aims to realize Tanjung Batu village, Tenggarong Seberang District, Kutai Kartanegara Regency as an Independent Village in environmentally friendly livestock cultivation. This community service is carried out through Focus Group Discussions (FGD), implements Appropriate Technology product on SMEs and Maggot cultivation business actors as an alternative feed for high protein and inexpensive fish, and conducts social media management training for Youth Organizations. In addition, this PPTTG activity is also filled with training on the use of organic waste counting equipment and the cultivation of Maggot larvae for breeders and training for creative youth groups to use social media as a means of promoting SMEs products or promoting Tanjung Batu village as an independent village. The outputs produced in this PkM include improving the performance of partners, village officials, SMEs, and creative groups to produce more innovative and planned performance. So that Tanjung Batu village has a competitive advantage in human resources and produces high quality products that are marketed.